1996
DOI: 10.1021/jo960633p
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oxidizing Reagent Based on Potassium Ferrate(VI)1

Abstract: A new, efficient preparation has been devised for potassium ferrate(VI) (K(2)FeO(4)). The ability of this high-valent iron salt for oxidizing organic substrates in nonaqueous media was studied. Using benzyl alcohol as a model, the catalytic activity of a wide range of microporous adsorbents was ascertained. Among numerous solid supports of the aluminosilicate type, the K10 montmorillonite clay was found to be best at achieving quantitative formation of benzaldehyde, without any overoxidation to benzoic acid. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
147
0
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(174 citation statements)
references
References 56 publications
7
147
0
14
Order By: Relevance
“…Diammonium 2,2 0 -azinobis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS, 98%), and humic acid (HA) were purchased from SigmaeAldrich; while montmorillonite K 10 (MMT) was from Acros Organics. Potassium ferrate (Fe(VI), >95%) was prepared by wet chemical synthesis (Delaude and Laszlo, 1996). Buffer chemicals and all other reagents used in the experiments were of analytical grade.…”
Section: Standards and Materialsmentioning
confidence: 99%
“…Diammonium 2,2 0 -azinobis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS, 98%), and humic acid (HA) were purchased from SigmaeAldrich; while montmorillonite K 10 (MMT) was from Acros Organics. Potassium ferrate (Fe(VI), >95%) was prepared by wet chemical synthesis (Delaude and Laszlo, 1996). Buffer chemicals and all other reagents used in the experiments were of analytical grade.…”
Section: Standards and Materialsmentioning
confidence: 99%
“…Diammonium 2,2 0 -azinobis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS, 98%) was obtained from Tokyo chemical industry (Shanghai, China). Potassium ferrate (Fe(VI)) was prepared by wet chemical synthesis (Delaude and Laszlo, 1996). It has a purity of above 95% as Fe(VI) (w/w), which was determined by the direct 510 nm method (3 ¼ 1150 M À1 cm À1 ) at the pH value of 9.1 AE 0.1 (5 mM K 2 HPO 4 /1 mM borate) (Rush and Bielski, 1986).…”
Section: Standards and Reagentsmentioning
confidence: 99%
“…Oxidation of Amines Catalyzed by PWAA Since PWAA efficiently promoted the epoxidation of allylic alcohols, we applied this oxidation system to secondary amines. [45][46][47][48][49][50][51][52][53][54][55][56] Oxidation of secondary amines is the most straightforward method and the direct route to prepare nitrones, which are important substrates for the synthesis of nitrogen-containing bioactive compounds. It was beforehand confirmed that no oxidation of dibenzylamine (11a) with hydrogen peroxide was observed at room temperature.…”
Section: Epoxidation Of Allylic Alcoholsmentioning
confidence: 99%